2020
DOI: 10.30802/aalas-cm-18-000136
|View full text |Cite
|
Sign up to set email alerts
|

Betamethasone Treatment for Atopic Dermatitis in Gut Microbiota Transplanted Mice

Abstract: Gut microbiota composition correlates strongly with essential disease parameters in the oxazolone-induced mouse model for atopic dermatitis. The phenotype of this model can be transferred to germ-free mice with a gut microbiota transplant to achieve high and low responding mice. Therefore, the production of high responding mice through gut microbiota transplantation may be seen as a tool to reduce group sizes or increase power in intervention studies by increasing effect size. We sought to determine whether h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition to limited animal numbers and diversity, efforts to compare the severity of dermatitis between animals and evaluate treatment success were stymied by the lack of an established skin-scoring system in pigs. Dermatologic scoring systems are well-utilized in spontaneous and induced disease models in rodents, allowing for the evaluation of treatment efficacy and comparison of severity between animals, but are not established in swine ( Hampton et al., 2012 ; Debes et al., 2020 ; Oh et al., 2021 ; Feng et al., 2022 ). While pigs are prone to develop numerous dermatologic diseases, primarily post-mortem scoring trials have been developed for the evaluation of carcass characteristics at slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to limited animal numbers and diversity, efforts to compare the severity of dermatitis between animals and evaluate treatment success were stymied by the lack of an established skin-scoring system in pigs. Dermatologic scoring systems are well-utilized in spontaneous and induced disease models in rodents, allowing for the evaluation of treatment efficacy and comparison of severity between animals, but are not established in swine ( Hampton et al., 2012 ; Debes et al., 2020 ; Oh et al., 2021 ; Feng et al., 2022 ). While pigs are prone to develop numerous dermatologic diseases, primarily post-mortem scoring trials have been developed for the evaluation of carcass characteristics at slaughter.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiomes are correlated with pro- and anti-inflammatory cytokines, even before the induction of skin inflammation, and the composition of the intestinal microbiome was found to be altered upon oxazolone-induced AD [ 67 ]. Moreover, Debes et al recently showed that intestinal microbiome transplants to germ-free mice reflected the AD-responding phenotype from donor mice [ 68 ]. In another study, ovalbumin-induced AD was aggravated in mice with intestinal microbiome dysbiosis established by the oral administration of antibiotics [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present world, this can be difficult as too little is known about what would be the perfect phenotype for a specific disease phenotype in rodents, and whether this would be relevant for the human patients. However, it might within certain research types, such as atopic dermatitis, for which it is known that there is a strong correlation between microbiota and phenotype (Lundberg et al 2012 ), be possible to conserve and transplant high responder microbiotas (Zachariassen et al 2017 ), as these can be shown to respond to interventions (Debes et al 2020 ). The transfer is not necessarily an easy task, as the colonization rate from mice to mice is approximately only 60—80%, and the transplanted mice seem to have a Firmicutes overgrowth (Lundberg et al 2017 ).…”
Section: Microbiota Impact On Reproducibility Of Various Immunologicamentioning
confidence: 99%